2021
DOI: 10.1109/tqe.2021.3092710
|View full text |Cite
|
Sign up to set email alerts
|

Single-Qubit Fidelity Assessment of Quantum Annealing Hardware

Abstract: As a wide variety of quantum computing platforms become available, methods for assessing and comparing the performance of these devices are of increasing interest and importance. Inspired by the success of single-qubit error rate computations for tracking the progress of gate-based quantum computers, this work proposes a Quantum Annealing Single-qubit Assessment (QASA) protocol for quantifying the performance of individual qubits in quantum annealing computers. The proposed protocol scales to large quantum ann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 40 publications
0
21
0
Order By: Relevance
“…In addition to the fundamental impacts of open quantum systems, the D-Wave hardware documentation highlights five other sources of deviations from ideal system operations called integrated control errors (ICE) [44], which include: background susceptibility; flux noise; Digital-to-Analog Conversion quantization; Input/Ouput system effects; and variable scale across qubits. Consequently, it has long been observed that output distributions of the QA hardware produced by D-Wave Systems are reminiscent of a Gibbs distribution of the input Hamiltonian H Ising [13][14][15][16]18] with a hardware-specific effective temperature of β ≈ 10 [17,45]. The prevailing interpretation of the hardware's output distribution is the Freeze Out model, which proposes that the output reflects a quantum Gibbs distribution occurring at an input-dependent point towards the end of the annealing process where some small amount of σ x i remains [46].…”
Section: B Quantum Annealing and Samplingmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition to the fundamental impacts of open quantum systems, the D-Wave hardware documentation highlights five other sources of deviations from ideal system operations called integrated control errors (ICE) [44], which include: background susceptibility; flux noise; Digital-to-Analog Conversion quantization; Input/Ouput system effects; and variable scale across qubits. Consequently, it has long been observed that output distributions of the QA hardware produced by D-Wave Systems are reminiscent of a Gibbs distribution of the input Hamiltonian H Ising [13][14][15][16]18] with a hardware-specific effective temperature of β ≈ 10 [17,45]. The prevailing interpretation of the hardware's output distribution is the Freeze Out model, which proposes that the output reflects a quantum Gibbs distribution occurring at an input-dependent point towards the end of the annealing process where some small amount of σ x i remains [46].…”
Section: B Quantum Annealing and Samplingmentioning
confidence: 99%
“…However, these quantum Gibbs distributions are inaccurate when targeting a desired classical Gibbs distribution for sampling applications [6,18,52,53]. The recent insight from [17] is that when this hardware is operated at a low-energy scale (i.e., |J|, |h| ≤ 0.050) it behaves as a thermalized classical Gibbs sampler from H Ising but suffers from a notable amount of distortion from instantaneous noise in the local field parameters, h, on the order of 0.036 [45,54], resulting in so-called noisy Gibbs samples.…”
Section: B Quantum Annealing and Samplingmentioning
confidence: 99%
See 3 more Smart Citations